Transactivation of the epidermal growth factor receptor by cag+ Helicobacter pylori induces upregulation of the early growth response gene Egr-1 in gastric epithelial cells. Issue 10 (29th April 2005) - Keates, S; Keates, A C; Nath, S; Peek, R M; Kelly, C P
Abstract : Background and aims: Helicobacter pylori, in particular cytotoxin associated gene ( cag ) + strains, have been shown to enhance gastric epithelial cell proliferation in vivo, an effect that likely contributes to gastric carcinogenesis. Early growth response gene 1 (Egr-1) is a crucial regulator of cell growth, differentiation, and survival, which is known to play a role in carcinogenesis and cancer progression. The aims of this study were to: (1) examine whether H pylori could upregulate Egr-1 in gastric epithelial cell lines; (2) determine whether there was a differential response to infection with different strains; (3) examine the role of the cag pathogenicity island in this process; and (4) elucidate the molecular mechanisms leading to Egr-1 upregulation. Methods and results: We found that infection of AGS cells with cag+ H pylori resulted in a rapid (1–2 hours) but transient increase in Egr-1 mRNA and protein levels whereas coculture with cag− isolates did not elicit this response. Furthermore, two independent cagE− isogenic mutants of H pylori also demonstrated impaired ability to upregulate Egr-1. Upregulation of Egr-1 protein was inhibited by the extracellular regulated kinase (ERK)1/2 inhibitor PD98059 and overexpression of dominant negative MEK1 downregulated Egr-1 luciferase reporter gene activity. Treatment of AGS cells with the epidermal growth factor receptor (EGFR) kinase inhibitors PD153035 and AG1478 resulted in a reduction in H pylori mediated Egr-1 upregulation, demonstrating that EGFR transactivation plays a role in this early cellular process. Conclusions: Our findings show that cag+ H pylori cause rapid induction of Egr-1 in gastric epithelial cells which may contribute to H pylori mediated pathogenesis.